JONATHAN EDWARDS MEETS DIETRICH BONHOEFFER: TRUE RELIGION OR NON-RELIGIOUS CHRISTIANITY? - Burnell, Joel (Jonathan Edwards studies, 2014)
It seems that Jonathan Edwards and Dietrich Bonhoeffer are on opposite ends of the religious spectrum. But is that really the case? This article explores how Edwards’ Religious Affections might fare when subjected to a Bonhoefferian critique of religion, and compares his views on true religion to Bonhoeffer’s proposal for non-religious Christianity. Do they complement or contradict each other? A discussion of Edwards’ views on true religion and Bonhoeffer’s seminal ideas on the future of non-religious Christianity leads to examining three crucial areas of comparison: public vis-à-vis ecclesial theology; regeneration vis-à-vis "God’s righteousness and kingdom on earth"; and "Holy practice" vis-à-vis "prayer and doing justice among human beings". Despite obvious differences in their historical time, traditions, and terminology, Edwards’ and Bonhoeffer’s respective views and practice of following Jesus, summarized for convenience under the phrases "true religion" and "non-religious Christianity, share much in common.